2005
DOI: 10.1038/nrd1719
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase, a promising drug target for neurological disorders

Abstract: Rho kinases (ROCKs), the first Rho effectors to be described, are serine/threonine kinases that are important in fundamental processes of cell migration, cell proliferation and cell survival. Abnormal activation of the Rho/ROCK pathway has been observed in various disorders of the central nervous system. Injury to the adult vertebrate brain and spinal cord activates ROCKs, thereby inhibiting neurite growth and sprouting. Inhibition of ROCKs results in accelerated regeneration and enhanced functional recovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
494
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(508 citation statements)
references
References 116 publications
7
494
1
6
Order By: Relevance
“…HA1077 is in clinical use for managing cerebral vasospasm associated with subarachnoid hemorrhage and is under clinical trial for acute ischemic stroke [37], among other conditions. Application of Y27632 has also been investigated for promotion of neurite outgrowth and axonal regeneration [38][39][40][41][42][43][44][45] and inactivation of Rho or ROCK signaling promoted functional recovery and/or axonal regeneration after neural injuries [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…HA1077 is in clinical use for managing cerebral vasospasm associated with subarachnoid hemorrhage and is under clinical trial for acute ischemic stroke [37], among other conditions. Application of Y27632 has also been investigated for promotion of neurite outgrowth and axonal regeneration [38][39][40][41][42][43][44][45] and inactivation of Rho or ROCK signaling promoted functional recovery and/or axonal regeneration after neural injuries [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the Rho/ROCK signaling pathway has attracted much attention in various research fields, and more than 2,000 articles have been published; many of which focus on ROCK function in the cardiovascular system, central nervous system, cancers and embryonic development. Several excellent recent reviews have covered large aspects [11,33,51,78,94,97,113,123]. The up to date progress in the translational research has demonstrated that ROCK is an important therapeutic target for the treatment of various cardiovascular diseases and neurological disorders, cancers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…neural growth cone collapse, neurite retraction, and even neuron death (Wahl et al, 2000;Mueller et al, 2005;Chan et al, 2007). Thus, inflammatory factors from inflammatory pathway up-regulation or activation were negative for neurite outgrowth (Alamdary et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…ROCK over-activation or upregulation was reported to be correlated with neural injury and most neural disorders (Mueller et al, 2005;Kubo and Yamashita, 2007). Otherwise, ROCK inhibition by Y27632 or fasudil and ROCK down-regulation by small interfering RNA (siRNA) were both able to promote neural fiber regeneration and functional recovery (Fournier et al, 2003;Hiraga et al, 2006;Impellizzeri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%